2018
DOI: 10.1002/mc.22883
|View full text |Cite
|
Sign up to set email alerts
|

Functional significance of Hippo/YAP signaling for drug resistance in colorectal cancer

Abstract: Colorectal cancer is a leading cause of cancer-related death worldwide. While early stage colorectal cancer can be removed by surgery, patients with advanced disease are treated by chemotherapy, with 5-Fluorouracil (5-FU) as a main ingredient. However, most patients with advanced colorectal cancer eventually succumb to the disease despite some responded initially. Thus, identifying molecular mechanisms responsible for drug resistance will help design novel strategies to treat colorectal cancer. In this study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 35 publications
0
37
1
Order By: Relevance
“…Similarly, Wang et al 34 reported that YAP expression was highest in HCT116, LS174T, LoVo, SW480 and SW620 colon cancer cell lines and that the capacity of these cells for proliferation, metastasis and invasion was markedly reduced by silencing YAP expression. In addition, YAP has been identified as a driver gene for EMT, which may contribute to the invasion and metastasis of cancers, 20,35 including gastric cancer, 36 breast cancer 37 and pancreatic cancer. [38][39][40] The results of the present study conclusively demonstrate that the SNHG11-induced malignant behaviour of CRC is accompanied by alterations in YAP phosphorylation and total YAP protein levels.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Wang et al 34 reported that YAP expression was highest in HCT116, LS174T, LoVo, SW480 and SW620 colon cancer cell lines and that the capacity of these cells for proliferation, metastasis and invasion was markedly reduced by silencing YAP expression. In addition, YAP has been identified as a driver gene for EMT, which may contribute to the invasion and metastasis of cancers, 20,35 including gastric cancer, 36 breast cancer 37 and pancreatic cancer. [38][39][40] The results of the present study conclusively demonstrate that the SNHG11-induced malignant behaviour of CRC is accompanied by alterations in YAP phosphorylation and total YAP protein levels.…”
Section: Discussionmentioning
confidence: 99%
“…The Hippo signaling pathway, first identified in Drosophila, was originally discovered to play a crucial role in regulating tissue growth; gradually it was found to be closely implicated in the modulation of multiple biological processes such as cell proliferation and apoptosis. [4][5][6][7] Mst1/2 (Mammalian Ste20-like 1 and 2), LATS1/2 (large tumor suppressor kinase 1/2), MOB1A/1B (MOB kinase activator 1A/1B) and SAV1 (salvador family WW domain-containing protein 1) are core components of Hippo signaling pathway, and their main role is to prevent the transportation of Yes-associated protein (YAP) to nuclear, thereby inhibiting the transcription of its downstream genes. 8,9 Notably, studies have confirmed that Hippo/YAP signaling plays a crucial role in chemoradiotherapy resistance of tumors.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Notably, studies have confirmed that Hippo/YAP signaling plays a crucial role in chemoradiotherapy resistance of tumors. For example, Song et al 7 found that knockdown of YAP1 significantly enhanced the sensitivity of colorectal cancer LoVo-R cells, an acquired 5-fluorouracil resistant cell line. Fernandez et al 10 demonstrated that YAP conferred tumor cell radio-resistance and promoted cell ongoing proliferation after radiation in medulloblastoma.…”
Section: Introductionmentioning
confidence: 99%
“…YAP1 was known to be associated with therapy resistance of cancer treatment [16]. A number of studies demonstrated that increased nuclear localization of YAP-TAZ and higher transcriptional activities of YAP/TAZ target genes have been observed in therapyresistant tumors [16,29,30]. With regard to the relationship between YAP1 and PCa, Jiang et al conducted a mass spectrometry-based quantitative proteomic approach and used it to compare protein phosphorylation in orthotopic xenograft tumors grown in either intact or castrated mice [31].…”
Section: Discussionmentioning
confidence: 99%